Comparative analysis of evaluation methodologies in weapon collection programmes - Koyama, Shukuko (United Nations Institute for Disarmament Research, 2006)
Compares the results from two evaluation approaches of weapon collection programmes in which the incentives were based on commmunity development programmes. UNIDIR's participatory evaluations were compared to the more conventional interview technique applied by other organisations. Results show the two techniques to be complementary.